Curing of Plasmid pXO1 from Bacillus anthracis Using Plasmid Incompatibility - Liu, Xiankai; Wang, Dongshu; Wang, Huagui; Feng, Erling; Zhu, Li; Wang, Hengliang (PLOS ONE, 2012)
The large plasmid pXO1 encoding the anthrax toxin is important for the virulence of Bacillus anthracis. It is essential to cure pXO1 from B. anthracis to evaluate its role in the pathogenesis of anthrax infection. Because conventional methods for curing plasmids (e.g., curing agents or growth at elevated temperatures) can induce mutations in the host chromosomal DNA, we developed a specific and reliable method to eliminate pXO1 from B. anthracis using plasmid incompatibility. Three putative replication origins of pXO1 were inserted into a temperature-sensitive plasmid to generate three incompatible plasmids. One of the three plasmids successfully eliminated the large plasmid pXO1 from B. anthracis vaccine strain A16R and wild type strain A16. These findings provided additional information about the replication/partitioning of pXO1 and demonstrated that introducing a small incompatible plasmid can generate plasmid-cured strains of B. anthracis without inducing spontaneous mutations in the host chromosome.